The euro as an international currency - Francesco Papadia; Konstantinos Efstathiou (Bruegel, 2018)
Two questions should be answered in relation to the international role of the euro: is a more important international role for the euro worth pursuing, and what measures would achieve this result, if it is worth pursuing? The most significant benefit for the euro area if the euro played an increased international role would be less dependence on the dollar and a reduced ability of the United States to pursue its political objectives, which are possibly inconsistent with European Union objectives. Historically, international functions have been shared between currencies and the international weights of currencies have evolved according to a limited number of variables. The most important of these are the economic size of the issuing country, the level of development and stability of the underlying financial market, openness to capital movements, a policy stance that encourages currency internationalisation, and political and military power. With the exception of financial stability, these factors do not vary substantially in the short run and give rise to persistent, long-term trends. Thus, in the first twenty years of its existence, the euro has consistently been the second most used international currency, while the dollar has maintained the first position it has held since the second world war. The gap between the dollar and the euro is greatest in the invoicing of commodity trade and as vehicle for foreign exchange transactions, and smallest in cross-border payments. While the ranking of the dollar and the euro has not changed, the euro's share has fluctuated, particularly in its use in international finance, in correlation with the stability of the euro financial market. This has confirmed that a necessary condition for the euro to play a greater international role is the stability of the euro-area financial system. In addition, the completion of banking union, progress on capital markets union, the issuance of a common bond, and more generally the completion of the institutional architecture of the euro area and progress on a common foreign and defence policy, would promote a wider role for the euro. The European Central Bank should also move beyond its neutral attitude towards the international use of the euro. Most of these policies would have effects well beyond the international use of the euro and, while in principle desirable, are not easy to achieve. Proposals on the international role of the euro published in December 2018 by the European Commission were the start of a journey rather than a decisive step towards a greater international role for the euro.
Keywords: 330